2019
DOI: 10.1002/ejp.1454
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐fibre receptors expressing acid‐sensing ion channel 3 contribute to muscular mechanical hypersensitivity after exercise

Abstract: Background Delayed onset muscle soreness (DOMS) is characterized by mechanical hyperalgesia after lengthening contractions (LC). It is relatively common and causes disturbance for many people who require continuous exercise, yet its molecular and peripheral neural mechanisms are poorly understood. Methods We examined whether muscular myelinated Aδ‐fibres, in addition to unmyelinated C‐fibres, are involved in LC‐induced mechanical hypersensitivity, and whether acid‐sensing ion channel (ASIC)‐3 expressed in thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Despite the exact mechanisms are not fully understood, it has been postulated that the alteration of the muscle chemical milieu after exercise induced muscle damage (EIMD) (6), due to increase metabolites production and accumulation (i.e., prostaglandins, lactate, protons), could sensitize and or increase muscle nerve afferents and related nociceptor activity (4,7,8). Indeed, inflammation following muscle damage may cause mechanical hyperalgesia (tenderness and movement induced-pain) (9)(10)(11) better known as delayed onset of muscle soreness (DOMS) (12,13) that is suggested to be linked to an increased activity and sensitization of Aδ-(III) and C-fiber (IV) nerve endings (14,15). Indeed, inflammation, injuries or muscle damage events (as EIMD) are thought to induce afferent nerve sensitization with related increases in expression of purinergic 2X receptor (P2X), acid sensing-ion channel receptor (ASIC), transient receptors potential vanilloid channels receptors (TRPV) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the exact mechanisms are not fully understood, it has been postulated that the alteration of the muscle chemical milieu after exercise induced muscle damage (EIMD) (6), due to increase metabolites production and accumulation (i.e., prostaglandins, lactate, protons), could sensitize and or increase muscle nerve afferents and related nociceptor activity (4,7,8). Indeed, inflammation following muscle damage may cause mechanical hyperalgesia (tenderness and movement induced-pain) (9)(10)(11) better known as delayed onset of muscle soreness (DOMS) (12,13) that is suggested to be linked to an increased activity and sensitization of Aδ-(III) and C-fiber (IV) nerve endings (14,15). Indeed, inflammation, injuries or muscle damage events (as EIMD) are thought to induce afferent nerve sensitization with related increases in expression of purinergic 2X receptor (P2X), acid sensing-ion channel receptor (ASIC), transient receptors potential vanilloid channels receptors (TRPV) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Antagonist experiments with amiloride and capsazepine in this study showed that high NGF‐induced mechanical hyperalgesia involves TRPV1 and high GDNF‐induced mechanical hyperalgesia involved ASICs (possibly ASIC3, Matsubara et al . 2019), whereas mechanical hyperalgesia induced by the mixture of low NGF and low GDNF involved both receptor channels. In addition, previous single‐fibre experiments from our group showed that NGF sensitized mainly C‐fibre afferents innervating the muscle (Murase et al .…”
Section: Discussionmentioning
confidence: 97%
“…ASIC3 and ASIC1 have been reported to play a critical role in the development of acidic saline-induced muscular hyperalgesia [5557]. ASIC3 has been shown to be involved in the LC-induced muscular mechanical hyperalgesia [58]. Voilley et al .…”
Section: Discussionmentioning
confidence: 99%